Some performance indicators of Malawi indigenous goats under village and ranch conditions - Karua, S.K. (1989)
Goat performance in 6 villages around Bunda College and at lifidzi ranch in Salima was monitored during 1985 and 1986. In the villages age at first kidding was 15.0±1.9 months; season of the does own birth affected her age at first kidding on the ranch. Kidding percentage was 107 under village conditions and 175 on the ranch. Kidding interval was 44.9±11.3wk in the villages and 35.2±6.8 wk on the ranch. Season had a significant effect on kidding interval in the villages but to on the ranch. Village goat litter size was 1.35±0.5; on the ranch it was 1.38±0.5. In both systems litters were largest during the cool dry season (May or August) and smallest during the cool dry season (September or Novemebr). Birth weight of single born kids was 1.75±0.4 kg in the villages and 1.77±0.5 kg at the ranch. Birth weight was positively correlated to dam postpartum weight (r=0.58). Dams kidding multiples were heavier than those kidding singles. Kid mortality was different in different seasons in the villages but not on the ranch. Mortality was 11.0% in the villages and 20.1% on the ranch while abortion was 5.6% in the villages and 9.5% on the ranch.